Moving Fast With Frontier Technologies - United Nations Conference on Trade; Development (United Nations, 2023)
In the last two decades, the use of frontier technologies such as artificial intelligence, the Internet of things and energy from renewable sources has undergone significant growth, and this trend is expected to continue. However, there is still considerable concentration in these markets. The leading frontier technology providers are mostly firms from China, the United States of America and a few other developed countries, with little participation from developing countries. The same pattern is observed with regard to knowledge generation and trade. Governments of developing countries should take proactive action to increase preparedness to use, adopt and adapt such technologies and to take up the economic opportunities linked to them. Some of the challenges associated with the adoption of new technologies in developing countries are addressed in this policy brief, and some policy recommendations are proposed.